2003
DOI: 10.1046/j.1365-2915.2003.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the mitochondrial cytochrome oxidase I gene of Oestridae species causing obligate myiasis

Abstract: A 688-bp region of the mitochondrial cytochrome oxidase I gene was sequenced from larvae of 18 species of Oestridae causing obligate myiasis. Larvae belonged to the four Oestridae subfamilies (Cuterebrinae, Gasterophilinae, Hypodermatinae and Oestrinae), which are commonly found throughout the world. Analysis of both nucleotide and amino acid data was performed. Nucleotide sequences included 385 conserved sites and 303 variable sites; mean nucleotide variation between all species was 18.1% and variation within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 21 publications
5
68
0
Order By: Relevance
“…Wells and Sperling [13] reported intraspecific level of variation within the COI and COII sequence for chrysomyinae flies of below 1%. Likewise, Otranto et al [14], who used COI to distinguish between Hypoderma larvae, reported a rate of intraspecific variation ranging from 0.14% to 1.59%.…”
Section: Discussionmentioning
confidence: 99%
“…Wells and Sperling [13] reported intraspecific level of variation within the COI and COII sequence for chrysomyinae flies of below 1%. Likewise, Otranto et al [14], who used COI to distinguish between Hypoderma larvae, reported a rate of intraspecific variation ranging from 0.14% to 1.59%.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted as described previously (Otranto et al 2003a). Brießy, Ϸ20 mg of larval internal organs was processed with a commercial kit (Quantum Prep, AquaPure Genomic DNA kit, BioRad, Hercules, CA) after drying tissues at 60ЊC for 15Ј, and DNA was quantiÞed spectrophotometrically at 260 nm and stored at 4ЊC until molecular analysis.…”
Section: Methodsmentioning
confidence: 99%
“…PCR conditions for ampliÞcation of the three target genes were optimized by titration of MgCl 2 and primer concentrations, varying annealing temperatures and times and cycle numbers. Table 1 reports the sequences (5Ј to 3Ј) of the primers used to amplify the mitochondrial and ribosomal regions under examination (Simon et al 1994, Lunt et al 1996, Stevens and Wall 2001, Otranto et al 2003a.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, DNA-based approaches targeting the mitochondrial gene encoding for the cytochrome oxidase c subunit 1 (cox1) have been largely employed for the identification of insects ranked into several orders (Lunt et al 1996;Zhang and Hewitt 1996;Otranto et al 2003). A molecular investigation carried out on 13 species of Steganinae confirmed that cox1 gene is a useful marker in polymerase chain reaction (PCR)-coupled sequencing approaches for the unequivocal identification of the species ranked into the genus Phortica (Otranto et al 2008).…”
mentioning
confidence: 99%